(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Today, rapid changes have become the norm for domestic enterprises. They encourage them to search for new effective management tools and change the management paradigm in general. Under these circumstances, managing the development of an enterprise is an extremely challenging task for managers at all levels of management, as only those enterprises that are able to adapt their management system to new challenges and opportunities to improve performance will be able to survive. The modification of the basic elements of the management process is closely of the fundamental change in the defining parameters of the environment and the formation of new realities of business. The BANI world order requires the management of enterprises to develop new management models that would ensure rapid adaptation to new circumstances. The BANI world is an extremely unstable world order in which changes are chaotic under the influence of global systemic changes, and technology development is occurring at an extremely rapid pace. In order to survive in the BANI world, a business entity needs to adapt and reorient quickly, be flexible and anti-fragile, think non-linearly, and form emotional supports, including developing empathy and emotional intelligence. In this regard, the modern management paradigm should be based on a systemic and situational approach to management and managerial art. The main principles of effective work of a modern manager in the BANI world are: flexibility and adaptability; innovation; risk-orientation; dynamism; efficiency; complexity; stress resistance; care for the interests of society and environmental protection; impartiality of thinking. The most effective tools for ensuring the effective functioning of enterprises in the BANI world order are the Agile-approach, design thinking technology, and value approach. Changing business conditions require modern managers to have not only traditional "hard skills" and "soft skills" but also "meta skills". The main qualities required of a modern manager are adaptability; critical and creative thinking; empathy; high emotional and social intelligence; creativity; ability to build horizontal relationships with employees; and the ability to make informed management decisions in the face of limited information.